Motivations and Psychological Characteristics of Nondirected Uterus Donors From The Dallas UtErus Transplant Study. (December 2021) - Warren, Ann M.; McMinn, Kenleigh; Testa, Giuliano; Wall, Anji; Saracino, Giovanna; Johannesson, Liza
Introduction: Uterus transplantation has demonstrated success in clinical trials. Questions regarding how it should transition to a clinical procedure must be addressed. A critical element is an evidence regarding the psychological experiences of living uterus donors, especially donors who are nondirected (altruistic). Project aims: To describe the motivations for donation, psychological characteristics, and mental health history of nondirected living uterus donors in the Dallas UtErus Transplant Study (NCT02656550). Design: An observational design was used to evaluate 44 self-referred nondirected uterus donors for the uterus transplant program. The donors participated in a clinical interview with a licensed psychologist and completed assessment instruments for depression, anxiety, posttraumatic stress, health-related quality of life, and resilience at the time of evaluation. Results: Among the 11 donors, the median age was 36 years, 10 were married, 10 were of non-Hispanic/Latino ethnicity, and all had given birth (median of 2 children). The most frequent motivations for the donation were to provide another woman with the opportunity to carry her own child and to contribute to science. No participants met clinical criteria for depression, anxiety or posttraumatic stress but 4 reported current mental health conditions and 7 reported past or present treatment. Quality of life and resilience scores were above population norms. Conclusion: Women selected as nondirected uterus donors were motivated to help other women experience carrying their own child and to contribute to science. A minority of women reported mental health conditions and/or treatment, and this was determined not to exclude participation with uterus donation.